Интернет в социальных политиках и массовом сознании: гендерный анализ - Суковатая, В. (Социология: теория, методы, маркетинг, 2004)
The author discusses gender policy in the Internet, analyzes periods of cyber-feminism development, reveals differences between cyber-feminism and liberal feminism of the past century. The article shows how the Internet, video-games and high computer technologies affect post-soviet gender identity and the mass consciousness.